Grain size effect on structures and dielectric constants for nanocrystalline BaTiO3 ceramic. (July 2013) - Wang, L. M.; Deng, X. Y.; Li, J. B.; Zhang, G. Q.; Wang, C. P.; Su, K. F.
Abstract : Size effect on the crystalline phase contents has been investigated for BaTiO3 ceramics and varied from 100 to 8 nm by means of X-ray diffraction and Raman spectroscopy techniques. Mixed phases of tetragonal and orthorhombic at room temperature were corroborated by Raman spectroscopy. Rietveld refinement for X-ray diffraction data revealed that a locally orthorhombic structure preceded the globally tetragonal form with the grain decreasing, and a modified brick wall model was used to predict the dielectric constant between 100 and 8 nm, which demonstrated that grain boundary effects, coexisted structures took the dominant role in determining the ultrafine nanocrystalline BaTiO3 ceramics dielectric constant.